Caracterização de espécies do gênero Rhodnius Stal, 1859 (Hemiptera, Reduviidae, Triatominae) pelo método MALDI-TOF-MS - Souza, Éder dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Triatominae são insetos hematófagos que transmitem a doença de Chagas. Entre os 19 gêneros da subfamília, aqueles com maior importância epidemiológica em relação à disseminação de Trypanosoma cruzi são Panstrongylus, Rhodnius e Triatoma. Dentre esses três gêneros, Rhodnius é o que apresenta maiores dificuldades para a definição específica, assim existe a necessidade de facilitar a identificação das espécies desse gênero. Neste estudo, a metodologia MALDI-MS foi utilizada para identificar 12 espécies de Rhodnius, dentre as 20 admitidas. A metodologia MALDI-MS permitiu a caracterização específica por meio da identificação de peptídeos e proteínas, a partir de quatro diferentes métodos de extração: A) Acetonitrila/ácido fórmico (ACN/AF), B) Acetonitrila/ ácido trifluoroacético (ACN/TFA), C) Isopropilamida/ácido fórmico (IPA/AF), e D) Metanol/ácido fórmico (MeOH/AF), e quatro tipos de matrizes MALDI/TOF: ácido α-ciano-4-hidroxicinâmico (CHCA), ácido sinápico (SA), 6-aza-2-tiotimina (ATT) e 2,6-di-hidroxiacetofenona (DHAP). Os experimentos foram realizados combinando os quatro solventes e quatro matrizes para selecionar a melhor extração/matriz de MALDI. A aplicação da técnica MALDI-TOF-MS, pela abordagem espectrométrica digital combinada com métodos quimiométricos foi capaz de distinguir com precisão as 12 espécies de Rhodnius. Assim, tendo em vista os resultados obtidos, a metodologia utilizada neste trabalho pode ser aplicada com rapidez, eficiência e para a identificação de espécies de Rhodnius.

Triatominae are hematophagous insects involved in the transmission of Chagas disease. Among the 19 genera of the subfamily, those with the highest epidemiological importance regarding the dissemination of Trypanosoma cruzi are Panstrongylus, Rhodnius, and Triatoma. Of these three genera, Rhodnius presents the greatest difficulties for specific identification. Thus, there is a need to overcome the difficulties in identifying phenotypes of similar species of this genus. In the present study, the MALDITOF MS methodology was used to identify 12 Rhodnius species, among the 20 admitted. The MALDI-TOF MS methodology allowed specific characterization through the identification of peptides and proteins, starting from four different methods of extraction: (A) acetonitrile/formic acid (ACN/AF), (B) acetonitrile/trifluoroacetic acid (ACN/TFA), (C) isopropyl/formic acid (IPA/AF), and (D) methanol/formic acid (MeOH/AF), and four types of MALDI-TOF matrices: α-cyano-4-hydroxycinnamic acid (CHCA), sinapic acid (SA), 6-aza-2-thiothymine (ATT), and 2,6-dihydroxyacetophenone (DHAP). The experiments were performed by combining the four solvents and four matrices to select the best MALDI extraction/matrix. The application of the MALDI-TOF MS technique, through the digital mass spectrometry approach combined with chemometric tools, such as partial least squares-discriminant analysis (PLS-DA), was able to discriminate 12 species of Rhodnius genus, which are difficult to identify using morphological characteristics. Thus, in view of the results obtained, the methodology described in the presente article can be applied with speed and efficiency for the discrimination of Triatominae species.
Characterization of species of the genus Rhodnius Stal, 1859 (Hemiptera, Reduviidae, Triatominae) by the MALDI-TOF-MS method
Keywords: Triatominae; Rhodnius; Espectrometria de massas; MALDI-TOF-MS; Quimiometria; Mass spectrometry